Bahaya Hamba Bersandar Pada Amal: Perspektif Khauf dan Raja’ - Yusuf, Moh (Mahad Aly Al Fithrah Press, 2020)
Khauf andraja' are among the elements of a structural composition of the human soul. The elements are provided by the Creator. These two elements will appear in humans in a certain condition or state of human experience. When khauf is excessive and dominates the human soul, it will lead to despair and result in disaster. Meanwhile, the raja'that propagates uncontrollably will lead to arrogance and turns into a loss. The emergence of khauf domination begins with the God servants’ attitude of excessively relying on their deeds or abilities. Meanwhile, the emergence of uncontrollably propagating raja' is caused by the same attitude towards the deeds. This character of dependence has made humans have minimum efforts towards Allah’s grace and His role as the Maker of the absolute policy of the acceptance and rejection of human deeds. There is a need for a continuous balance between khauf and raja' in order to eliminate the attitude of relying on the deeds and to build a comfortable inner harmony which lead to the mahabbah.